Peer Learning: An Effective Teaching-Learning Method for Improving Ability in Arterial Blood Gases Interpretation - Mauliandari, Riana; Sumarwati, Made; Upoyo, Arif Setyo (Nurse Media Journal of Nursing, 2020)
Background: Competent nurses are expected to be able to interpret arterial blood gases (ABGs). The benefits of peer learning, an innovative teaching-learning method today, have long been recognized. However, to date, no studies have compared the effect of this method and the traditional classical method in interpreting ABGs. Purpose: This study aimed to compare the effect of peer learning and classical learning methods on the nurses’ ability to interpret ABGs. Method: This was a quasi-experimental research with pre and post-test design. Forty ward nurses were invited in the peer learning method group, and another 40 ward nurses were invited in the classical learning method group through a randomization process. Data were collected using a questionnaire before and after the educational intervention. The classical class was taught by an experienced trainer, while peer groups, divided into groups of 5-6, were taught by one member of each group who obtained the best pre-test score and received special training first. The analysis of data was performed by t-test.Result: The result showed that after the intervention, the mean score of interpreting ABGs in the peer learning group increased by 3.18±1.12 (p<0.001), while in the classical learning method, it only increased by 2.32±0.988 (p<0.001). Although there were significant increases in ABGs analysis’s ability in both groups, the peer teaching-learning group demonstrated a significantly greater improvement in interpreting ABGs (p<0.001).Conclusion: The peer learning method facilitates a more significant improvement in the nurses’ ability for ABGs interpretation. Peer learning is appropriate as one of the methods in clinical education for nurses.